Synthesis and evaluation of tumor-homing peptides for targeting prostate cancer - KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (SPRINGER WIEN, 2021)
High toxicity caused by chemotherapeutic drugs and the acquisition of drug resistance by cancer cells are the major drawbacks in cancer therapy. A promising approach to overcome the posed barriers is conjugating tumor-homing peptides to drugs or nanocarriers. Such high-affinity peptides can specifically target surface markers overexpressed by cancer cells, ensuring a rapid and cancer-specific uptake of the drugs. Since prostate-specific membrane antigen (PSMA) is overexpressed by aggressive prostate cancer cells, targeting this surface protein with peptide conjugates can lead to the development of effective strategies against prostate cancer. In this study, we aimed to determine which PSMA-binding peptide among peptides 563, 562 and 9-mer, show the highest selectivity towards PSMA using 22Rv1 prostate cancer cells, a cell line with moderate PSMA levels. Tumor-homing peptides were synthesized by fluorenylmethoxycarbonyl-based solid-phase peptide synthesis (Fmoc-SPPS) strategy, and evaluated for their prostate cancer cell-specific targeting efficiencies by flow cytometry. Our results showed that the PSMA-binding capacity of peptide 563 was superior to those of 562, 9-mer, and 5-mer; therefore, can be utilized as a potent-targeting agent not only in the treatment of high PSMA positive but also moderate PSMA positive prostate cancer tumors.
Keywords: Prostate cancer; Tumor-homing peptides; Prostate-specific membrane antigen